(untitled) (Research, Society and Development, 2023)
The Brazilian Society of Cardiology, in its most current data, indicates that the major cause of death in Brazil are the Cardiovascular Diseases (CVD). In surgical cases, in the postoperative period, there are treatments aimed at reestablishing the functionality of the individual undergoing cardiac surgery. One of the techniques used in cardiorespiratory rehabilitation is inspiratory muscle training (IMT). The aim of this study is to analyze the effects of IMT in the postoperative period of cardiac surgeries, as well as the best treatment parameters, due to the importance of cardiorespiratory rehabilitation after surgical procedures. A bibliographic review of the scope type was performed, of the scientific materials, published in indexed journals, between the years 2008 to 2023 (last 15 years), free of charge, having as reference the databases: PEDro, PubMed and SciELO. After applying the inclusion and exclusion criteria, the study sample was composed of 4 articles, where 77% of them (3 articles) were published in the last 5 years, thus, already subtending a scarcity of studies on the subject. Through this review, it was possible to evidence in the literature positive effects of the use of IMT in patients in the PO of cardiac surgeries, but more studies are still needed to concretely determine the use of the aforementioned technique in these cases.